ChemInform Abstract: Metals on Graphene and Carbon Nanotube Surfaces: From Mobile Atoms to Atomtronics to Bulk Metals to Clusters and Catalysts. Issue 9 (4th March 2014) - Sarkar, Santanu; Moser, Matthew L.; Tian, Xiaojuan; Zhang, Xixiang; Al‐Hadeethi, Yas Fadel; Haddon, Robert C.
Abstract Review: 84 refs.